Student affairs assessment : theory to practice - Henning, Gavin; Roberts, Darby M. (New York, NY : Routledge, 2024)
"This second edition of Student Affairs Assessment: Theory to Practice provides updated content that reflects current student affairs assessment practice and signals the direction in which the field is headed. Chapters feature foundational concepts of assessment design, outcomes, and data collection methods while also addressing current topics in student affairs assessment such as the prevalence of data analytics through higher education and equity-centered assessment. In addition, this volume further broadens the scope of the assessment process by highlighting the impact of culturally responsive ethics and indigenous paradigms. Ultimately, this book provides student affairs staff with the grounding they need to integrate assessment into how they design and monitor the programs, services, and activities they create to contribute to students' development. A useful reference for implementing assessment of co-curricular programs and services, this book is an excellent guide for student affairs practitioners and experienced assessment professionals to develop their assessment skill and knowledge"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Student affairs services -- United States -- Evaluation; Student affairs services -- United States -- Administration; Student affairs administrators -- United States